Management of upper extremity peripheral vascular disease: a multimodality approach - Upganlawar, Prasad; Rahalkar, Ashwinee; Joshi, Sneha; Khatri, Simran (International Surgery Journal, 2020)
Background: It is estimated that more than 200 million people suffer from peripheral vascular disease worldwide. However very few studies are available on upper extremity vascular disease, thus making it an under diagnosed and under treated condition. Methods: In the present study we included 20 participants suffering from upper limb peripheral vascular disease and managed them with multi-modality approach involving general surgeon, interventional radiologist and vascular surgeon for medical line of management, thrombolysis and thrombo-embolectomy procedures. Results: In the present study we observed that early management of these patients with medical management, interventional radiology and embolectomy procedures helped in limb salvage. However alarmingly high number of patients (35%) landed up in amputation because of low index of suspicion and delayed referral. Conclusions: A high level of suspicion and early referral to a tertiary care centre where multi-modality facilities like interventional radiology and vascular surgeon are available should be done.